A utopia da liberdade de expressão num suposto estado democrático de direito / The utopia of freedom of expression in an allegedly democratic state - Santana, Selma Pereira de (Revista do Programa de Pós-Graduação em Direito, 2015)
The latest demonstrations in Brazil have rekindled the debate on the State’s recourse to repressive action. The purpose of this article is to establish that the attempts to classify such conduct as terrorist betray the State’s obliviousness to the fundamental rights of assembly and expression. The methodology used is the bibliographical and documentary descriptive research. The central issue focuses on the fact that Criminal Law has been the instrument used by the Three Branches to silence protests. Social protests are legitimate under the Constitution, as long as they abide by the limits imposed therein. It is the State’s responsibility to ensure that these rights can be exercised. Rather than solve social problems, attempting to silence a dissatisfied society transports them to a yet more complex dimension in which the frustration toward, and distrust of, institutions are translated into violence.